Implementasi React JS dalam Mengembangkan Front-End Website PT XYZ - Sekar Kinanti, Virandita; Setyadi, Resad; Widiasari, Lisna (LPPM & Fakultas Teknologi Informasi UNSAP, 2023)
Websites have become one of the most important marketing and communication tools for companies in today's digital era. PT XYZ, a company engaged in information technology, realized how important it is to have an attractive, interactive, and easy-to-use website to increase client outreach and strengthen their brand image. Previously, PT XYZ had their own company website, but there was no adequate maintenance of the website. As a result, the information displayed was not updated regularly and the appearance of the website was less interactive. The purpose of the research is to develop the front-end of PT XYZ's website using the React JS framework, with a focus on improving attractiveness, responsiveness, and user-friendliness. The result of this research is a PT XYZ’s website with a more attractive front-end display than before. Development was carried out using the Agile Scrum system development method, which ensures the project runs efficiently and adaptively to the company's needs. With this development, PT XYZ is expected to more effectively interact with clients and be able to compete in a competitive market